IMPLEMENTASI FUNGSI ACTUATING DAKWAH DI PANTI ASUHAN AR-ROHMAH NGALIYAN SEMARANG - Aniisah, Nurul; Mutiara Savitri, Fania (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This research examines the implementation of the actuating da'wah function at the Ar-Rohmah Ngaliyan Orphanage in Semarang, with the aim of understanding its implementation and obstacles. Using qualitative methods, data was collected through interviews, observation and documentation, then analyzed using data reduction, data presentation and verification techniques. The research results show that the function of actuating da'wah is implemented effectively through sincere motivation, harmonious coordination, and cooperation in preaching. The role of leaders like KH Parsin Abdullah is important in building an Islamic spirit and synergy between administrators, teachers and foster children. The da'wah program is based on moral development and collaboration with Islamic boarding schools to create a conducive environment. Management support through direction, evaluation, training and use of digital technology expands the reach of da'wah. The obstacles faced include internal and external factors such as the quality of human resources and management of infrastructure. Penelitian ini mengkaji implementasi fungsi actuating dakwah di Panti Asuhan Ar- Rohmah Ngaliyan Semarang, dengan tujuan memahami pelaksanaan dan kendalanya. Menggunakan metode kualitatif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis dengan teknik reduksi data, penyajian data, dan verifikasi. Hasil penelitian menunjukkan bahwa fungsi actuating dakwah diterapkan secara efektif melalui motivasi tulus, koordinasi harmonis, dan kerja sama dakwah. Peran pemimpin seperti KH Parsin Abdullah penting dalam membangun semangat Islami dan sinergi antara pengurus, pengajar, dan anak asuh. Program dakwah berbasis pembinaan akhlak dan kolaborasi dengan pondok pesantren menciptakan lingkungan kondusif. Dukungan pengurus melalui arahan, evaluasi, pelatihan, dan pemanfaatan teknologi digital memperluas jangkauan dakwah. Kendala yang dihadapi meliputi faktor internal panti dan eksternal seperti kualitas SDM dan manajemen sarana prasarana.